POLITWEETS: social media as a platform for political engagement between Victorian politicians and citizens. Issue 2 (2nd April 2016) - Lukamto, William; Carson, Andrea
ABSTRACT: Political parties and candidates' adoption of social media technologies engender both optimism and concern about voter engagement in Australia. On one hand, scholars have expressed hope for a more democratic politics freed from traditional media's gatekeeping role; on the other, researchers find political communication through social media generally fails to transcend politics 1.0. Following international studies, Australian scholarship focused on candidates' use of Twitter and Facebook for political campaigning has identified a largely unfulfilled potential for a more participatory public sphere. This article contributes original research to this question of online political engagement by examining Victorian state politicians' social media use during both non-election and election periods. We undertook quantitative content analysis and social networks analysis of politicians' Facebook and Twitter use in 2014. We find state politicians like their federal and other state counterparts are rapidly adopting digital technologies, particularly Facebook, for political communication. Yet, despite the significant increased social media use by Victorian politicians for public communication purposes, we find that similar to other recent Australian studies the extent of political engagement between politicians and voters on these social media sites remains low. We identify two related factors that impede political engagement in the digital sphere, they are citizens' negative comments and politicians' long-standing desire to control the political message.